Benzoate Concentration and Cooperativity by a Substrate for Benzoate 1,2-dioxygenase from Benzoate-Degrading Rhodococcus Opacus 1CP - V. Emelyanova Elena; P. Solyanikova Inna (Journal of Biotechnology and Biomedical Science, 2017)
We explored the effect of a change in substrate-benzoate (as sole carbon and energy source) concentration in growth medium on the activity of benzoate 1,2-dioxygenase (BDO) of R.opacus 1CP cells, where BDO is the enzyme mediated the initial attack of benzoate. The activity of the enzyme was estimated by a change of respiration of whole freshly harvested bacterial cells (growth of the cells on benzoate) in response to injection of benzoate. It was shown that when concentration of growth substrate-benzoate decreased from 6 g/L to 250 mg/L, the curves of the dependency of the response rate to benzoate on the initial concentration of benzoate demonstrated that kinetics of the process changes from hyperbolic saturation kinetics, or typical Michaelis-Menten kinetics, to sigmoidal dependency of V on S. The semisaturation constant as a characteristic of the strength of substrate binding with BDO changed simultaneously. These changes were accompanied by the increase in the Hill coefficient from 1.02 up to 3.06, hence positive kinetic cooperativity by a substrate was observed for BDO of R.opacus 1CP cells. The influence of this type of cooperativity on viability of rhodococcus in natural environment and causes of the changes mentioned are discussed. It was hypothesized that an increase in substrate concentration in the medium for the growth of the bacterium not only stimulated synthesis of the inducible enzyme (BDO) in the cell but also led to the change in BDO conformation followed by the change in interaction between substrate-binding active sites of enzymes.
Keywords: R. opacus 1CP